A Study of Internationally-published English Textbooks from the Perspective of English as a Lingua Franca Concerning Content and Pedagogy - 羅文杏(Wen-Hsing Luo) (Jiao ke shu yan jiu, 2017)
This study aims to examine internationally-published textbooks used at the tertiary level in Taiwan, especially in regard to content and pedagogy, from the perspective of English as a lingua franca (ELF). The English textbooks analyzed were used in English courses at a university where the study was conducted. This study employs textbook analysis, interviews with teachers, and class observations to determine (1) how and to what extent internationally-published textbooks reflect an ELF perspective, and (2) how course instructors treat the subject matter and activities presented in the textbooks to reflect an ELF perspective when taking into account the learners and the learning context. The study reveals that the internationally-published textbooks partially reflect an ELF perspective, but overlook the importance of raising learner awareness of ELF and the use of intercultural communication strategies. As for the adoption of the textbooks, the study finds that the teachers mainly taught the texts and reading exercises included in the units and would select and re-arrange unit content and exercises based on what they hoped to teach in their courses. Finally, implications that arise from the findings regarding the development of ELT materials with an ELF perspective are discussed.